2019
DOI: 10.1371/journal.pntd.0007882
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiologic characteristics associated with dengue during and outside the 2016 outbreak identified in health facility-based surveillance in Ouagadougou, Burkina Faso

Abstract: BackgroundIn Africa, the magnitude of dengue virus (DENV) transmission is largely unknown. In Burkina Faso, several outbreaks have been reported and data are often based on findings from outbreak investigations.MethodsTo better understand dengue epidemiology and clinical characteristics in Burkina Faso, a fever surveillance study was conducted among patients aged 1–55 years, who presented with non-malarial febrile illness at five primary healthcare facilities in Ouagadougou, Burkina Faso from December 2014 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 34 publications
2
44
0
2
Order By: Relevance
“…According to the World Health Organization, 1266 suspected cases, 1061 positive cases by dengue rapid diagnostic test (RDT: TDR in French) and 15 deaths were reported in 2016 [26]. In 2017, 9 029 suspected cases, 5773 dengue RDT-positive cases and 18 deaths (case fatality rate = 0.2%) were reported throughout the country [26,27]. The number of deaths due to dengue would likely have been lower if health workers had been better trained.…”
Section: Dengue In Burkina Faso (West Africa)mentioning
confidence: 99%
“…According to the World Health Organization, 1266 suspected cases, 1061 positive cases by dengue rapid diagnostic test (RDT: TDR in French) and 15 deaths were reported in 2016 [26]. In 2017, 9 029 suspected cases, 5773 dengue RDT-positive cases and 18 deaths (case fatality rate = 0.2%) were reported throughout the country [26,27]. The number of deaths due to dengue would likely have been lower if health workers had been better trained.…”
Section: Dengue In Burkina Faso (West Africa)mentioning
confidence: 99%
“…At the same time, a surveillance study conducted by Lim et al. in adjacent areas in Ouagadougou from December 2014 to February 2017 encompassing the WHO reported outbreak of August–November 2016 reported 2,929 fever cases during both outbreak and non-outbreak periods; 25.3% (740/2,929) were dengue-positive [ 11 ]. Seventy-three percent (540/740) of the dengue-positive cases were laboratory-confirmed and 27.0% (200/740) were classified as probable dengue; among these 42.8% (317/740) were confirmed by RT-PCR and the remainder by paired ELISA [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, and specifically in Burkina Faso, several studies have shown that a significant proportion of febrile illnesses are non-malarial [24][25][26] and thus becoming a major public health concern because the possibility of misdiagnosis and mistreatment of NMFI as malaria cases, specifically in the infant population [27]. Among these NMFI, we can cite dengue, typhoid fever, salmonellosis, Zika infection and recently COVID-19 which have become endemic in Burkina Faso [28][29][30]. To the best of our knowledge, the effects of free healthcare interventions on NMFI consultations have not been studied yet.…”
Section: Introductionmentioning
confidence: 99%